Wspieranie postawy twórczej rodziców dzieci z niepełnosprawnością poprzez arteterapię - Ochman, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2025)
A child’s disability is a difficult experience for parents. It requires continuous reorganization of the world in a way adequate to the child’s needs and requirements, which is often a difficult situation for parents. The emerging frustration and crisis mean that many parents cannot cope emotionally by existing circumstances. That is why it is extremely important to support them and make it possible to adapt to the constantly changing situation in the most effective way. The answer to the need for direct impacts may be art therapy, focused on providing emotional support and developing the creative basis. To ensure effective support for parents of children with disabilities, it is necessary to recognize their preferences, needs and expectations. The purpose of the research presented in the article is to learn about the opinions on creativity and determine the differences in the intensification of the creative attitude of parents of children with disabilities, parents of preschool children and students not boring children. Research problems were formulated for such a specific purpose, referring to: defining the concept of ‘creativity’, impact of creativity on everyday functioning, experiences of the respondents in developing your own creative attitude and the level of severity of this attitude. The exploration uses a diagnostic survey method with survey technique. The culmination conducted allowed to determine the differences in the scope of these issues and question the proposal of support through the art therapy of parents of children with disabilities.